2014
DOI: 10.1002/sec.1001
|View full text |Cite
|
Sign up to set email alerts
|

Optimal multiuser spread-spectrum data hiding in digital images

Abstract: In this work, we intend to carry out optimized spread-spectrum concealment of multiuser data under a given digital image. First, the overall image is pre-processed into transform-domain small blocks from which host vectors are obtained via zig-zag scanning vectorization. Multiuser data hiding is performed in the generated host vectors. Under this data hiding system model, we give an orthogonal set of embedding spread-spectrum signatures that achieves maximum sum signalto-interference-plus-noise ratio at the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, previous works have shown that feature normalisation and features selection improve performance of classification [19,31]. Equation (29) shows the used feature normalisation…”
Section: Performance Of the Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous works have shown that feature normalisation and features selection improve performance of classification [19,31]. Equation (29) shows the used feature normalisation…”
Section: Performance Of the Proposed Methodsmentioning
confidence: 99%
“…These methods include Hide4PGP [24], Steghide [21], integer to integer wavelet (i2i) [25]. Also, different spread spectrum methods have been proposed in the literature [5,[26][27][28][29][30]. Among them the DCT-based robust watermarking method (COX) [5], spread spectrum watermarking (SSW) [26], spread spectrum in the frequency domain (SS+DCT) [27], and multi carrier spread spectrum (MCSS) as implemented in [30] were tested in this study.…”
Section: 𝑛[𝑚] = 𝑠[𝑚] − 𝑐[𝑚]mentioning
confidence: 99%
“…So it would be very difficult to remove the watermark signal without damaging the host audio integrity. However, traditional SS watermarking methods severely face the host interference problem . As in the case of audio watermarking, the audio signal is very sensitive to additive manipulations.…”
Section: Introductionmentioning
confidence: 99%